2018
DOI: 10.1589/jpts.30.675
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference in factors affecting the medial longitudinal arch height of the foot in healthy young adults

Abstract: [Purpose] Medial longitudinal arch (MLA) height is associated with various injuries and diseases and gender differences, if any. This study aimed to examine factors affecting the MLA height associated with gender differences in healthy subjects with no orthopedic disorders. [Subjects and Methods] This study included 36 healthy adults (19 males, 17 females; mean age, 21.8 ± 3.6 years; body mass index, 21.1 ± 2.0 kg/m2). Their height, body weight, foot length, muscle strength of the tibialis posterior muscle (TP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 29 publications
3
9
0
2
Order By: Relevance
“…In this study, a very weak correlation was obtained between arch height ratio and toe flexor strength. Our results confirmed a similar tendency to the results reported by Nagano et al18 ) . On the other hand, while Uritani et al19 ) reported reliability as the cause of the very weak correlation, other factors include: (1) toe length, which determines whether or not the participant is able to grasp the bar for measurement with five toes, (2) those with long toes were able to lift the bars by bending the toes and the bar could not be drawn horizontally, and (3) muscles that act adjunctively, such as the tibialis anterior and tibialis posterior muscles, were thought to be influential.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this study, a very weak correlation was obtained between arch height ratio and toe flexor strength. Our results confirmed a similar tendency to the results reported by Nagano et al18 ) . On the other hand, while Uritani et al19 ) reported reliability as the cause of the very weak correlation, other factors include: (1) toe length, which determines whether or not the participant is able to grasp the bar for measurement with five toes, (2) those with long toes were able to lift the bars by bending the toes and the bar could not be drawn horizontally, and (3) muscles that act adjunctively, such as the tibialis anterior and tibialis posterior muscles, were thought to be influential.…”
Section: Discussionsupporting
confidence: 94%
“…Nagano et al18 ) showed a correlation between arch height ratio, toe flexor strength, and tibialis posterior muscle strength in females. Toe flexor strength was measured by pulling the bar connected to the dynamometer using the toes.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, we found MTPJ ROM is more significant in female patients. Previous studies have reported females have greater joint mobility of the foot and higher flaccidity foot ligaments than males [22] and analysis of foot radiographic images further proved the gender difference [23]. But due to the cross-sectional study design, we could not draw the conclusion regarding the cause and effect relationship between increased MTPJ ROM and development to PF.…”
Section: Discussionmentioning
confidence: 74%
“…The relationship between toe deformation and decreased toe flexor strength has been demonstrated by Mickle et al [13]. Toe flexor strength is also positively correlated with arch height [11,19]. Hence, assessing foot muscle function by measuring foot morphological characteristics, including foot length, foot width, truncated foot length, and navicular height, etc., can result in better understanding of the in-depth relationships between foot muscle strength and foot morphological characteristics and can provide references for athlete selection.…”
Section: Introductionmentioning
confidence: 93%
“…Toe flexor muscles comprise the intrinsic and extrinsic foot muscles [10], which are deemed as local stabilizers and global movers, respectively [4]. Toe flexor strength is considered an important factor affecting walking and standing abilities and balance stability [11]. Specifically, the weakness of toe flexor muscles may cause pain and movement problems [12] and increase the risk of falls in elderly individuals [13].…”
Section: Introductionmentioning
confidence: 99%